Pengembangan Buku Suplemen Berbasis Cerita Bergambar pada Mata Pelajaran IPAS di Kelas IV Sekolah Dasar - Norholis, Norholis; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (AS-SABIQUN, 2023)
This research and development aims to produce a supplementary book product based on illustrated stories in the subject of IPAS on the material of Indonesia's cultural wealth in class IV Elementary School which is feasible to use to assist the learning process in the independent curriculum. The method used is the Research and development (R&D) method by adapting the ADDIE model. 3 expert validators, 3 classroom teachers in the classroom, and 94 students were sampled in this study. strategies for collecting data through questionnaires and interviews. The results of research and development obtained a validity assessment according to the material expert validator in the content/material aspect obtained a percentage value of 82.23% with the criteria "Very Valid", according to the language expert validator in the language presentation aspect obtained a percentage value of 87.15% with the criteria "Very Valid", according to the design expert in the design aspect obtained a percentage value of 86.67% with the criteria "Very Valid", and according to the design expert validator in the graphical aspect obtained a percentage value of 82.50% with the criteria "Very Valid". These results are supported by the results of product trial activities and received a "Very Good" response from the teacher with a percentage value of 93.70% while responses from small group students obtained a percentage value of 85.52% which is the criterion of "Very Good", and large group responses obtained a percentage value of 88.81% which is the criterion of "Very Good". Therefore, it can be said that this picture story-based supplement book is suitable for use in the learning process.